Entire Dirichlet Series of Rapid Growth and New Estimates for the Measure of Exceptional Sets in Theorems of the Wiman–Valiron Type
For entire Dirichlet series of the form \(F( z ) = olimits_n = 0^ + ∞ a_n e^zλ _n ,0 λ _n + ∞ , n → + ∞ \) , we establish conditions under which the relation F( σ + iy